A new species of the genus Centrolene (Amphibia: Anura: Centrolenidae) from Ecuador with comments on the taxonomy and biogeography of Glassfrogs - Cisneros-Heredia, Diego F.; Mcdiarmid, Roy W. (Zootaxa, 2006)
We describe a new species of Glassfrog, Centrolene mariaelenae n. sp., from the Contrafuerte de Tzunantza, southeastern Ecuador. The new species is assigned to the Centrolene gorzulai species group, a clade previously known only from the Guayana Shield region, because the parietal peritoneum is transparent and the hepatic peritoneum is covered by guanophores. We analyze the diversity patterns of Glassfrogs from eastern Ecuador. The distribution of the new species herein described supports previous hypothesis of a biogeographical connection between the Andes and the Guayana Shield for various groups of plants and animals; particularly a relationship between the Guayana Shield and the sandstone outcrops mountain ranges of southeastern Ecuador and northeastern Peru. We also comment on the infrageneric and generic classification of Glassfrogs, and propose the new combinations Centrolene balionotum n. comb., Cochranella antisthenesi n. comb., and Cochranella pulverata n. comb.